Analysis of Curriculum and Learning Patterns Related to Morals in Madrasah Level Ibtidayah in 2013 - Safwandy Nugraha, Mulyawan; Hamdani Bakhtiar, Yusup (Yayasan Mentari Madani, 2024)
The 2013 curriculum has been thoughtfully created to address the demands and problems of the twenty-first century. To accomplish its goals, an analytical research must, nevertheless, acquire a fresh, all-encompassing viewpoint. Finding the appropriate viewpoint for executing the curriculum at the lower MI level is the goal of this study. This study uses an analytical descriptive methodology and is conducted in a library. The analysis's findings indicate: First, Madrasah Ibtidaiyah's 2013 curriculum for its lower-class Morals topics, which incorporates integrated theme content, is suitable in terms of both psychology and philosophy. Second, this curriculum emphasizes a scientific approach to learning, but in order to assist students engage with the actual world and assess their learning through thorough and genuine assessments, it places a strong emphasis on Contextual Teaching Learning (CTL).